Phase 3 Randomized Trial Results of DTX401 AAV Gene Therapy for the Treatment of GSDIa - John J. Mitchell; Jose E. Abdenur; Foekje de Boer; Monica Boyer; Margo Sheck Breilyn; María‐Luz Couce; Diva D. De Leon; Terry G. Derks; Areeg El‐Gharbawy; Andrea B. Haijer‐Schreuder; Karen Loechner; Nicola Longo; et al. (Journal of Inherited Metabolic Disease, 2026)
ABSTRACT Glycogen storage disease type Ia (GSDIa) is a rare, life‐threatening inherited carbohydrate metabolism disorder caused by biallelic pathogenic G6PC gene variants resulting in deficiency of glucose‐6‐phosphatase. DTX401 is an investigational AAV8 vector containing the human G6PC gene. DTX401‐CL301 is a pivotal, phase 3, double‐blind, randomized, placebo‐controlled trial of DTX401 in patients ≥ 8 years with GSDIa. The primary endpoint was percent change from Baseline to Week 48 in daily cornstarch intake for the DTX401 versus placebo group. Participants were randomly assigned (1:1) to blinded DTX401 or placebo. After the 48‐week Primary Efficacy Analysis Period (PEAP), participants crossed over in a blinded manner for an additional 48‐week blinded Crossover Period. Following randomization: 21 participants received DTX401; 25 received placebo. At Week 48, DTX401 treatment resulted in a statistically significant least squares (LS) mean (SE) daily cornstarch intake reduction of 41% (4.6) versus 10% (4.1) for Placebo ( p < 0.0001). Clinical meaningfulness was evidenced by a mean desired percent reduction in daily cornstarch intake among those reporting in Baseline interviews ( n = 33) of 45% (median = 41%). Greater and faster reductions in cornstarch were observed at Week 96 for the Crossover DTX401 group compared with the DTX401 group in the PEAP. The DTX401 safety profile was acceptable, and expected hepatic reactions consisting of transaminase elevations were managed with prophylactic corticosteroids. Treatment with DTX401 resulted in both a statistically significant and clinically meaningful reduction in cornstarch intake in the 48‐week PEAP versus placebo, with greater cornstarch reductions in both groups at Week 96.